2013
DOI: 10.1088/1741-2560/10/6/066011
|View full text |Cite
|
Sign up to set email alerts
|

System identification of the nonlinear dynamics in the thalamocortical circuit in response to patterned thalamic microstimulationin vivo

Abstract: Objective Nonlinear system identification approaches were used to develop a dynamical model of the network level response to patterns of microstimulation in-vivo. Approach The thalamocortical circuit of the rodent vibrissa pathway was the model system, with voltage sensitive dye imaging capturing the cortical response to patterns of stimulation delivered from a single electrode in the ventral posteromedial thalamus. The results of simple paired stimulus experiments formed the basis for the development of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Our laboratory has recently demonstrated that VNS can be used to induce a rapid, general improvement of thalamic sensory processing ( Figure 1 ). This is a continuation of our team’s studies investigating the effects of the LC-NE system on thalamocortical circuitry ( Rodenkirch et al, 2019 ), a critical stage for sensory processing and perception ( Saalmann and Kastner, 2011 ; Stanley et al, 2012 ; Wang et al, 2012 ; Millard et al, 2013 ; Kelly et al, 2014 ; Ollerenshaw et al, 2014 ; Wimmer et al, 2015 ; Rikhye et al, 2018 ). These studies found that direct activation of the LC-NE system (electrical or optogenetic), in a continuous tonic fashion, optimized intrathalamic dynamics for sensory processing.…”
Section: Transient Modulation Of Sensory Processing Occurs Rapidly Up...mentioning
confidence: 78%
“…Our laboratory has recently demonstrated that VNS can be used to induce a rapid, general improvement of thalamic sensory processing ( Figure 1 ). This is a continuation of our team’s studies investigating the effects of the LC-NE system on thalamocortical circuitry ( Rodenkirch et al, 2019 ), a critical stage for sensory processing and perception ( Saalmann and Kastner, 2011 ; Stanley et al, 2012 ; Wang et al, 2012 ; Millard et al, 2013 ; Kelly et al, 2014 ; Ollerenshaw et al, 2014 ; Wimmer et al, 2015 ; Rikhye et al, 2018 ). These studies found that direct activation of the LC-NE system (electrical or optogenetic), in a continuous tonic fashion, optimized intrathalamic dynamics for sensory processing.…”
Section: Transient Modulation Of Sensory Processing Occurs Rapidly Up...mentioning
confidence: 78%
“…This decrease in discrimination performance may be due to the reduction in time for the animal to accumulate evidence concerning the direction of the whisker deflection to make Go or No-Go decisions (Gold and Shadlen 2007). Neurons in the thalamus and cortex of the whisker pathway display strong sensitivity to the velocity of whisker movement; thus another explanation is that the velocity of the shortest duration stimulus was too strong and saturated the neural responses within the pathway, leading to deterioration in performance (Lee and Simons 2004;Millard et al 2013;Pinto et al 2000;Stüttgen and Schwarz 2008;Zheng et al 2015). However, the peak velocity of whisker movement associated with stick-slip events (repeated sticking then high-acceleration slipping over surfaces when rats whisk across objects) is comparable to the highest velocity used in this study (i.e.,~1,200°/s) (Jadhav et al 2009;Ritt et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if an accurate model of feedforward network dynamics could be incorporated into the controller, reliable control over fast events might be possible with a modestly sized population of cells, a slower feedback loop, and standard opsin variants. This is a viable approach in circuits for which predictive models of feedforward network dynamics are available, such as early visual, auditory, and vibrissal pathways ( Wu et al, 2006 ; Millard et al, 2013 ), or, for which accurate input/output relationships can be deduced in situ using real-time system identification ( Grosenick et al, 2015 ). Additionally, control algorithms that incorporate models of feed-forward neural dynamics will be more capable of stabilizing firing in unstable circuits, such as epileptic networks, without total cessation of ongoing activity.…”
Section: Discussionmentioning
confidence: 99%